Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/jca.56093
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR promotes gefitinib resistance through modification of EZH2 and silencing p16 and p21 in non-small cell lung cancer

Abstract: The long non-coding RNA Hox transcript antisense intergenic RNA (HOTAIR) plays a critical role in tumorigenesis as well as drug resistance in various cancers. However, the molecular mechanism by which HOTAIR induces gefitinib resistance in non-small cell lung cancer is to date unclear. In the present study, we revealed that HOTAIR is upregulated in gefitinib-resistant lung cancer cells and over-expression of HOTAIR enhances gefitinib resistance in lung cancer cells. In addition, the overexpression of HOTAIR pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…p21 is a well-known WAF1/CIP1 (activating factor/cyclindependent kinase inhibitory protein-1) that was found to be vital for modulating cell cycle progression [17,18]. Early research on non-small cell lung cancer (NSCLC) revealed that in well-differentiated tumors, p21 is overexpressed [19] and stimulates tumor growth suppression via p53 activity, consistent with its cell cycle arrest activity [20]. Nevertheless, other studies have suggested that some pathways are not dependent on p53 and lead to p21 induction [20].…”
Section: Introductionmentioning
confidence: 99%
“…p21 is a well-known WAF1/CIP1 (activating factor/cyclindependent kinase inhibitory protein-1) that was found to be vital for modulating cell cycle progression [17,18]. Early research on non-small cell lung cancer (NSCLC) revealed that in well-differentiated tumors, p21 is overexpressed [19] and stimulates tumor growth suppression via p53 activity, consistent with its cell cycle arrest activity [20]. Nevertheless, other studies have suggested that some pathways are not dependent on p53 and lead to p21 induction [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are reported effects of drugs on histone H3 lysine-methylation, including H3K9me3 and H3K27me3 [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ], which are inconsistent. There are no reports on the effect of MTX on histone-H3 lysine-methylation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the levels of the histone H3K9me3 and H3K27me3 were decreased in methionine-addicted cancer cells when treated with rMETase [ 3 , 10 ]. There are previous reports on the relationship of drug resistance and the levels of H3K9me3 and H3K27me3, but they are not consistent [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. There are no reports on the effect of MTX on histone H3 lysine-methylation.…”
Section: Introductionmentioning
confidence: 97%
“…8). [269][270][271][272] Zheng et al found that the poor prognosis in NSCLC patients was closely related to overexpression of LncRNA FTH1P3, which can inhibit TIMP3 protein by recruiting LSD1 and increased cell resistance to gefitinib. 269 Moreover, HAS2-AS1 also inhibited EphB3 by recruiting LSD1, promoting tumorigenesis and gefitinib-resistance in NSCLC.…”
Section: Histone Demethylases (Hdmts)mentioning
confidence: 99%